The unconventional secretory machinery of fibroblast growth factor 2 - Nickel, Walter (Traffic, 2011)
Unconventional secretory proteins represent a subpopulation of extracellular factors that are exported from eukaryotic cells by mechanisms that do not depend on the endoplasmic reticulum and the Golgi complex. Various pathways have been implicated in unconventional secretion including those involving intracellular membrane-bound intermediates and others that are based on direct protein translocation across plasma membranes. Interleukin 1β (IL1β) and fibroblast growth factor 2 (FGF2) are classical examples of unconventional secretory proteins with IL1β believed to be present in intracellular vesicles prior to secretion. By contrast, FGF2 represents an example of a non-vesicular mechanism of unconventional secretion. Here, the author discusses the current knowledge about the molecular machinery being involved in FGF2 secretion. To reveal both differential and common requirements, this review further aims at a comprehensive comparison of this mechanism with other unconventional secretory processes. In particular, a potentially general role of tyrosine phosphorylation as a regulatory signal in unconventional protein secretion will be discussed.
Gesehen am 22.09.2022